Study of catalytic activity of ultrafine iron powders in liquid hydrocarbon synthesis; Catalysis for Renewable Sources: Fuel, Energy, Chemicals (CRS-4) - Burlutsky N. P. Nikita Pavlovich (2017, 2017)
Title screen